Geographic versus institutional drivers of nitrogen footprints: a comparison of two urban universities. (15th April 2020) - MacDonald, Graham K; Talbot, Julie; Moore, Tim R; Arsenault, Julien; McCourt, Sibeal; Goertzen, Aidan; Kessler-Nadeau, Max Émile; Manaugh, Kevin; Maranger, Roxane; Robinson, Brian E
Abstract: Excess reactive nitrogen (N) is linked to a myriad of environmental problems that carry large social costs. Nitrogen footprint tools can help institutions understand how their direct and indirect activities are associated with N release to the environment through energy use, food, and transportation. However, little is known about how geographic context shapes the environmental footprints of institutions. Defining the system boundaries over which institutions are responsible and able to control individual drivers of N footprints is also a challenge. Here, we compare and contrast the circa 2017 N footprints for two research intensive universities located in Montréal, Canada, with a combined full-time equivalent campus population of ∼83 000. Our estimate of McGill University's N footprint (121.2 t N yr −1 ) is 48% greater than Université de Montréal's (74.1 t N yr −1 ), which is also reflected on a per capita basis (3.3 and 1.6 kg N capita −1 yr −1, respectively). Key institutional factors that explain the differences include McGill's larger residential and international student populations, research farm, and characteristics of its on-campus fuel use. We use a series of counterfactual scenarios to test how shared urban geographic context factors lead to an effective reduction of the N footprints at both universities: the relatively small direct role of both institutions in food intake on campus (29%–68% reduction compared to a counterfactual scenario), energy from hydroelectricity (17%–21% reduction), and minimal car commuting by students (2%–3% reduction). In contrast, the near-zero N removal from the municipal wastewater system effectively increases the N footprints (11%–13% increase compared to a modest N removal and offset scenario). Our findings suggest that a shared geographic context of a dense city with plentiful off-campus housing, food options, and access to hydroelectricity shapes the absolute N footprints of Montréal's two main universities more than the divergent institutional characteristics that influence their relative N footprints.